2018
DOI: 10.1002/cam4.1364
|View full text |Cite
|
Sign up to set email alerts
|

CGB5 expression is independently associated with poor overall survival and recurrence‐free survival in patients with advanced gastric cancer

Abstract: The human CGB5 gene encodes chorionic gonadotropin (hCG)β 5, which is aberrantly expressed in trophoblastic neoplasm and in some non‐trophoblastic neoplasms. Fucntional studies observed that it involved tumor initiation, growth, and metastatic outgrowth. In this study, using data from the International Cancer Genome Consortium (ICGC) and the Cancer Genome Atlas (TCGA)‐stomach adenocarcinoma (STAD), we assessed the independent prognostic value of CGB5 expression in patients with primary gastric cancer (GC). Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…It has been considered as an independent prognostic factor for GC, which is consistent with our results[ 25 ]. Furthermore, CGB5 is correlated with a poor prognosis in patients with advanced GC[ 26 , 27 ]. It has been reported that LGR6 might be involved in the development of GC via the PI3K/AKT/mTOR axis[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been considered as an independent prognostic factor for GC, which is consistent with our results[ 25 ]. Furthermore, CGB5 is correlated with a poor prognosis in patients with advanced GC[ 26 , 27 ]. It has been reported that LGR6 might be involved in the development of GC via the PI3K/AKT/mTOR axis[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…β-hCG is well-known as an sensitive biomarker for trophoblastic tumors and diseases. Recently, studies have found that β-hCG was ectopically elevated in the histological and serological samples of renal cell carcinoma [14], hepatocellular carcinoma [15], gastric cancer [16] and colon cancer patients [17]. Moreover, β-hCG was regarded as a biomarker to surveille recurrence and follow-up of malignant germ cell and sex cord-stromal tumors as Class 2B evidence in the 2018 NCCN clinical practice guidelines in Ovarian Cancer [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high expression of CCL21 was related to lymph node metastasis and poor prognosis in GC patients [ 27 ]. CGB5 was found to be overexpressed in most GC tissues and was considered as an independent predictor of OS and recurrence-free survival for GC patients [ 28 ]. As the specific ligand of HER4, the role of NRG4 in GC remains controversial.…”
Section: Discussionmentioning
confidence: 99%